Progettare, realizzare e promuovere contenuti culturali digitali. Un esempio di didattica integrata: il progetto “Filosofia & Migrazioni” - Russo, Ada; Marras, Cristina (Umanistica Digitale, 2020)
The article describes the project Philosophy & Migration. Design, implement and promote digital cultural content (https://filosofiamigrazioni.wordpress.com/). The project started in 2017 thanks to the collaboration between researchers in History and Philosophy of the National Research Council (CNR) and the Italian Philosophical Society (SFI) - Roman Section. All the activities are characterized by the joint work of researchers, teachers and students, this cooperation is an example of integration of curricular programs in philosophy with the study of contemporary migrations and the development of skills in design and organizing digital content. The article focuses on the project and its model to stress the multiple connections between the world of research and the world of education; the complementarity and integration between knowledge and skills; the importance of a critical use of digital tools and methodologies. We also underline the criticalities and the difficulties we encountered in our work such as the still embryonic digital literacy of teachers and students, the inadequacy of the school infrastructures, the difficulty to use technologies in a critical way.